Level of Environmental Literacy of Students and School Community in Green Open Space: Is There any Difference between Both of Them? - Putra, N. S.; Sukma, H. N.; Setiawan, H. (Jurnal Pendidikan IPA Indonesia, 2021)
Environmental education aims to create people who have good environmental literacy. This study tries to explain previous studies related to how the level of students’ literacy and stakeholders’ literacy in green open space affects students' environmental literacy. This is descriptive research conducted in SMPN 2 Suayan. The purposes of this study are 1) to identify the environmental literacy of the students and the school community in the green open space 2) to identify the difference between students’ environmental literacy and school community in green open space. The sample consists of 70 students and 40 people from the school community. Measurement of environmental literacy is discussed in 3 domains, namely the domain of knowledge, attitudes towards the environment, and behavior towards the environment. The total number of instruments is 45 items. The reliability value of instruments for knowledge, attitude, and behavior domains are 0.874, 0.927, and 0.965, respectively, and are the high category. Collected data of students and school community were analyzed by using Microsoft Excel and SPSS. The difference in environmental literacy of students and school community in green open space was analyzed by using Mann-Whitney U Test. The environmental literacy value of students and school community are respectively 77.1% and 79.7% and are high category. The analysis on the achievement of environmental literacy scores shows that there are no significant differences in both groups. This concludes that the school community that has good environmental literacy will give a good influence on students’ environmental literacy and knowledge. The last, by knowing the roles of the school community and availability of green open space on achieving environmental literacy of students, all related stakeholders are suggested to upgrade the environmental literacy of the school community and support the availability of green open space in the school area.